KORELASI PENGALAMAN RESEPTIF BERLITERASI CERPEN DENGAN KETERAMPILAN MENULIS CERPEN SISWA KELAS VIII SMP NEGERI 6 KOTA SOLOK - Nofrizon, Anggi; Abdurrahman, Abdurrahman; Nurizzati, Nurizzati (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purposes of this study were (1) to describe the persentage of students receptive experience in short story literation in second grade of SMP 6 Solok. (2) to describe students skill of writing short story in second grade of SMP 6 Solok. (3) to know the correlation of students receptive experience of short story literation and students skill of writing short story in second grade of SMP 6 Solok. The data of this study were the score of questionnaire about receptive experience of short story literation and students essay about students skill writing short story. The primary source of data were written test of students in second grade of SMP 6 Solok. Data were collected by (1) giving the questionnaire in form of five possible answers. (2) giving the essay test about short story. The findings of this study about the students receptive experience in short story literation and students writing skill of short story of second grade of SMP 6 Solok were in good classification (80,02%) and average (55,55%).Â Kata kunci: Pengalaman Reseptif, Keterampilan Menulis